Double Standards in Moral Judgments Within Intimate Relationships: A Multifaceted Perspective - Yao, Shuchen; Dong, Da; Yang, Liping; Yin, Yating (Journal of NeuroPhilosophy, 2025)
In this opinion piece, we delve into the role of intimate relationships in shaping moral judgment, highlighting the notable disparity between appraisals of intimate others and strangers in instances of ethical transgressions. It contends that the double standard observed in these scenarios reflect the intricate interplay between human emotions and the adaptable nature of moral evaluation within different contexts. Drawing on the field of moral psychology, the analysis introduces pivotal theoretical frameworks, including moral reasoning, moral intuition, the hypotheses of moral universalism and moral favoritism, the dual-process theory of moral judgment, and a person-centered perspective on moral assessment. We center on pluralistic factors that influence moral judgment within intimate relationships, including emotion, cognition, value, perception of harm, perspective, and power dynamics. A notable incongruity is identified between the professed moral duties of people and their protective actions toward loved ones, with individuals frequently acting to defend intimate others despite holding conflicting moral principles. Besides, we conclude by exploring the repercussions of these double standards for modern legal systems.